Implementation of the Group Investigation Model in Arabic Language Learning to Strengthen 4C Competencies in Writing Skills - Sapitri, Aulia; Anggraini, Suci Nur; Harianto, Neldi; Al Qorin, Amami Shofiya; Rashid, Huda Salah (Universitas Islam Negeri Sunan Ampel Surabaya, Indonesia, 2026)
Writing skill (maharah al-kitabah) is one of the most complex skills in Arabic language learning because it requires the ability to organize ideas, think critically, and communicate meaning coherently. This study aims to analyze the implementation of Cooperative Learning using the Group Investigation (GI) model in strengthening 4C competencies—critical thinking, creativity, collaboration, and communication—in Arabic writing instruction. This research employs a qualitative approach with a descriptive design through library research. Data were collected from national and international journal articles published between 2020 and 2025 and analyzed using data reduction, data display, and conclusion drawing techniques. The findings indicate that the Group Investigation model is conceptually relevant to the characteristics of Arabic writing skills, as it encourages students to actively investigate topics, develop ideas collaboratively, and construct texts systematically. Furthermore, the integration of the GI model contributes to improving the quality of students’ writing in terms of idea development, language accuracy, and paragraph coherence, while simultaneously strengthening 4C competencies. Therefore, Group Investigation can be considered an innovative cooperative learning model that supports Arabic writing instruction aligned with the demands of 21st-century education.